Sunlight mediated degradation of spent wash using hydrothermally synthesized orthorhombic shaped Cu–TiO2 nanoparticles. (9th October 2020) - Takle, Shrikant P.; Apine, Onkar A.; Bankar, Digambar B.; Tarlekar, Aarti S.; Bhujbal, Namdeo N.; Kale, Bharat B.; Sonawane, Ravindra S.
Abstract : This method is suitable for the selective growth of orthorhombic shaped Cu–TiO2, which shows an excellent performance for the degradation of sugar industry waste. Abstract : Degradation of spent wash waste is a very essential but challenging task in the indian sugarcane distillery industry because of its awfully acidic pH, and intense brown colour with a strong unpleasant odour. Prior to discharge in the environment, its degradation using an efficient and cost effective method is important. A photo-catalytic degradation route could be a simple, cost effective alternative to conventional degradation processes. Cu-doped TiO2 was synthesised using a facile sol gel assisted hydrothermal method at various temperatures such as 120, 150 and 180 °C. Cu–TiO2 with doping concentrations of 0.5 to 5% were synthesized using the hydrothermal method. The physico-chemical properties of the synthesised Cu–TiO2 were investigated by using various characterization techniques. UV-visible analysis shows a red shift in the absorption wavelength in the case of Cu–TiO2 as compared with bare TiO2 . Structural and morphological analysis confirms the formation of anatase TiO2 with a nano-orthorhomb like morphology. The photocatalytic performance of the TiO2 and Cu doped TiO2 samples was evaluated for degradation of spent wash colour under natural solar light irradiation. Among all the Cu–TiO2 samples, 1% Cu–TiO2 synthesized at 150 °C exhibited the maximum degradation efficiency with almost 59% degradation of the spent wash in 5 h. The molecular weight of the colour compounds after degradation was monitored using gel permeation chromatography (GPC). The GPC fractions show low, medium, and high molecular weight coloured compounds with a strong hypsochromic shift. Identification of the compounds in each of the GPC fractions was studied using liquid chromatography mass spectrometry quadrupole time of flight (LC-MS Q-TOF).